Complex biochemical characteristics of broccoli and cauliflower - D. A. Fateev; A. E. Solovyeva; T. V. Shelenga; A. M. Artemyeva (Овощи России, 2020)
Relevance. A commonly cultivated and demanded type of vegetable crops – cabbage Brassica oleracea L. – in the process of evolution and domestication was divided into three clusters: leafy cabbage, headed cabbage and broccoli (cauliflower). According to modern data, Broccoli was developed by hybridization from collard greens and is the genetic precursor to cauliflower. Broccoli and cauliflower have a valuable biochemical composition and are recommended for daily consumption. The characteristic of cultures of Brassica oleracea L. (broccoli and cauliflower) is given according to the most important biochemical quality characteristics. Material and methods. The research material included 30 accessions of broccoli and 35 accessions of cauliflower from the VIR collection, reflecting the ecological, geographical and genetic diversity. Accessions were grown at the research and production base "Pushkin and Pavlovsk Laboratories VIR" (St. Petersburg), biochemical analysis was carried out in the laboratory of biochemistry and molecular biology VIR using gas chromatography/mass spectrometry. Results. The characterization of Brassica oleracea L. species (broccoli and cauliflower) is given according to the main most important biochemical quality characteristics. As a result of using of the modern gas chromatography/mass spectrometry approach to the study of the biochemical composition in samples of broccoli and cauliflower, about 136 components have been identified from the groups of organic acids, free amino acids, including essential, fatty acids, including essential, polyhydric alcohols, sugars, and also phenolic compounds, nucleosides, and others. Regularity in the accumulation of nutrient and biologically active substances by cultures of Brassica oleracea L., by cultivar types and individual samples were revealed. As a result of our research using modern techniques new data on the biochemical composition of broccoli and cauliflower were obtained. B.oleracea within the studied botanical varieties and cultivar types has a complex biochemical composition that characterizes them as accessions with potentially high value, which confirms the need for indepth control of the biochemical composition of plants when breeding new varieties. Accessions with the optimal component composition for balanced human nutrition, which are proposed to be used in breeding for quality, including obtaining varieties for healthy (functional) and therapeutic and prophylactic nutrition of the population of the Russian Federation were found.